DESCRIPTION OF THE DIFFICULTY OF STUDENTS' MATHEMATICS PROBLEM SOLVING ASSESSED FROM ADVERSITY QUOTIENT (AQ) - Amiratih Siti Aisyah; Riyadi Riyadi; Sri Subanti (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to determine the difficulty of solving mathematic problems among students AQ climbers, AQ campers, and AQ quitters. This type of research was qualitative research with a descriptive approach. The subject of this study is the 3rd grade of XI MIPA Batik High School 2 Surakarta in the academic year 2020/2021 which constitutes 6 students. The subject taking was done by giving an adversity quotient questionnaire. From the results of filling out the questionnaire, the subjects were categorized based on their AQ. Furthermore, given a mathematic problem-solving test. After seeing the test results, three subjects representing AQ climbers, AQ campers, and AQ quitters were selected purposively for further interviews. The results showed: 1) The climbers subject experienced two difficulties in solving mathematic problems, namely difficulties in understanding problems and difficulties in implementing plans. 2) The subject of the campers has three difficulties in solving mathematic problems, namely difficulties in understanding problems, difficulties in implementing plans, and difficulties in reviewing. 3) The quitters subject experiences four difficulties in solving mathematic problems, namely difficulties in understanding problems, difficulties in planning, difficulties in implementing plans and difficulties in reviewing, and difficulties in revisiting.